Association Between Oxidized LDL and Folate During Pregnancy. (April 2013) - Shiraishi, Mie; Haruna, Megumi; Matsuzaki, Masayo; Ota, Erika; Murayama, Ryoko; Watanabe, Etsuko; Sasaki, Satoshi; Yeo, SeonAe; Murashima, Sachiyo
High levels of oxidized low-density lipoprotein (ox-LDL) during pregnancy are a risk factor for preeclampsia. Ox-LDL levels might be affected by folate and total homocysteine (tHcy) levels because of their effects on oxygen free radicals. The relationships between ox-LDL and folate and tHcy during pregnancy, however, remain unclear. The present study investigated whether serum folate levels and plasma tHcy levels were associated with plasma ox-LDL levels in pregnant women. A sample of 137 healthy subjects with singleton pregnancies (age 30.3 ± 4.5 years) was recruited from a prenatal clinic in metropolitan Tokyo between June and October 2008. Their levels of plasma ox-LDL, plasma tHcy, and serum folate were measured, and lifestyle variables were obtained using a questionnaire. Dietary intake was assessed by means of a validated self-administered diet history questionnaire. A negative correlation between plasma ox-LDL levels and serum folate levels was found ( r s = −.218, p =.011). However, there was no association between plasma ox-LDL levels and plasma tHcy levels ( r s = .055, p = .525). The mean of the logarithmic ox-LDL levels was significantly lower among the participants taking folic acid–containing supplements regularly than among those who were not, after adjusting for confounding factors ( p = .024). Serum folate levels and folic acid supplementation might be associated with plasma ox-LDL levels, independent of tHcy levels. The association observed between ox-LDL and folate can be used as evidence for dietary instruction by prenatal care providers.